Utilizing Marxist-Leninist Viewpoints to Construct the Vietnamese People's Army in the Present Era - TRAN, Mong Nghi; LE, Thi Thuy Duong (Journal of Ecohumanism, 2024)
The formation of the military is a historical and social occurrence that possesses significant class attributes. According to the Marxist-Leninist texts, the armed forces are considered as a tool of organized violence controlled by the ruling class. They are trained, taught, and utilized to fulfill the purposes and ideals of the ruling class. Following the October Revolution, the establishment of the socialist state gave rise to a new kind of military known as the socialist army or the army of the working class. This army possessed inherent distinctions from prior armed formations, since it operated in alignment with the objectives of the proletariat and the socialist state. In accordance with Marxist-Leninist ideas, the construction of the socialist army must encompass all aspects of politics, ideology, organization, discipline, weapons, technological equipment, and science. This complete approach is necessary to safeguard the revolutionary accomplishments and the socialist rule. The directives outlined by the 13th National Congress of the Communist Party of Vietnam for developing a "streamlined, strong, and modern" army demonstrate the Party's ongoing adherence to Marxist-Leninist principles in establishing the Vietnamese People's Army at present. This study examines the essential elements and original aspects of applying these rules, which contribute to the protection of the Socialist Republic of Vietnam.